Intracorporeal esophagojejunostomy using hemi-double-stapling technique after laparoscopic total gastrectomy in gastric cancer patients - Ali, Bandar; Park, Cho Hyun; Song, Kyo Young (Annals of surgical treatment and research, 2017)
To present the feasibility and safety of Roux-en-Y esophagojejunostomy using hemi-double-stapling technique after laparoscopic total gastrectomy. We reviewed the outcomes from 58 consecutive patients with gastric cancer who underwent laparoscopic total gastrectomy. The clinicopathological characteristics including postoperative complications were examined. The mean age and body mass index were 57.3 ± 9.7 years and 23.7 ± 2.6 kg/m , respectively. The mean overall total operation was 199.8 ± 57.0 minutes. Intraoperative blood loss was 81.6 ± 56.3 mL and there was no open conversion. The patients' hospital stay was a mean 9.6 ± 2 days. The mean proximal margin of the specimens was 2.7 ± 1.8 cm. There were 3 cases (5.1%) of anastomosis leakage, but all were controlled successfully by endoscopic stent. The circular HDST technique is simple and reliable without any significant demerits with respect to safety concerns or difficulty of operation.